The Application Of Word Webbing Technique In Improving Students’ Achievement In Vocabulary At Mts Muhammadiyah 15 Medan - Nazli Fahada; Saidatul Hanim (Journal of Classroom Action Research, 2023)
To master vocabulary is influenced by many factors, many techniques and strategies such as playing scrabble, memorize new vocabulary by English song and word webbing technique also can be a way to master and memorize vocabulary. In this research, the researcher limits the study on the technique.    Word webbing technique is a way to help the students to think more creative to associate idea or words more easily. Word webbing approach is a way to assist the students of university to think greater innovative to companion thought or phrases more easily. Word webbing is a notion mapping of words, which is, normal through ability of webs and links. Word webbing is a approach that can be used to expand thinking or words. This method is beneficial for the students of university who favor or like to make higher their ideas or words, specially in getting to understand vocabulary. The goals of this research are  to understand if the students’ success in vocabulary can be accelerated through the application of phrase webbing approach or not. The research was once carried out only in one class with two cycles.  The archives have been taken from the first 12 months MTs Muhammadiyah 15  Medan. The real variety of the  students in the category used to be 27 students. The finding of the research is that Word Webbing Technique can help the students improve their vocabulary achievement. By making use of this Word Webbing Technique, the ranking of the students in vocabulary saved increasing from the pre- test until the post- test  seem to be at in each cycle. It was once proved through the use of the data which validated that the mean of the  students in the post- test  II (77.0) was higher than the post I (70.4) and additionally higher than pre- test (51.5).    Keywords : word webbing technique, vocabulary